The Correlation Between Nurses' Knowledge and Attitudes and the Provision of Patients' Spiritual Care in the High Care Unit - Rahmi, Hidayatul; Rebbi, Rebbi Permata Sari; Iqbal, Revi Neini; Rasyid, Willady (Journal of Health Sciences and Epidemiology, 2025)
Spiritual care is a vital aspect of holistic nursing, especially in critical care environments such as high care units (HCUs). While nurses' knowledge and attitudes are thought to influence the delivery of spiritual care, there is limited evidence in HCU settings. This study aimed to explore the relationship between nurses' knowledge, attitudes, and their implementation of spiritual care in HCUs. A cross-sectional correlational design was employed, involving 30 nurses working in hospitals in Padang City. Data were collected using a structured questionnaire that assessed nurses' knowledge, attitudes, and spiritual care practices. The Nurse Spiritual Care Therapeutics Scale (NSCTS) was utilized to measure the frequency of spiritual care practices. Descriptive statistics and chi-squared tests were applied for data analysis, with statistical significance set at p < 0.05. Results showed that 53.3% of nurses had good knowledge, 70.0% had positive attitudes, and 60.0% reported providing good spiritual care practices. Chi-square analysis revealed significant associations between knowledge and spiritual care practice (p = 0.031) and attitude and spiritual care practice (p = 0.012). These findings emphasize the importance of enhancing nurses' knowledge and attitudes toward spiritual care through targeted training, supportive policies, and the integration of spiritual care competencies into nursing curricula.